The impact of an audit committee's independence and competence on investment decision: a study in Bahrain - Abdullah Al-Hadrami; Ahmad Rafiki; Adel Sarea (Emerald Publishing Limited, 2020)
This study aims to investigate the impact of the audit committee's (AC) independence and competence on the company's investment decision-making in Bahraini-listed companies.A quantitative method is used, and crosssectional data are collected through a self-administered questionnaire survey. A stratified random sample technique is adopted with a total of 409 respondents from 39 listed companies. A descriptive analysis is used to identify the characteristics of the respondents, while the correlation analysis and linear regression analyses are used to test the model and explain the relationship between variables.It is found that the AC independence and AC competence have a positive and significant influence on investment decision-making.The AC’s independence and competence are importantly crucial for the decision-makers in improving the quality of financial reporting, internal control and audit. This may lead to the increase in investors' trust on financial reports and thereby making favorable investment decisions.